The coronavirus conundrum - The end of the COVID-19 pandemic? - The woman, the pregnant woman and the fetus - Vaccines - Future - Romero, José Pacheco (2022)
WHO Director-General Tedros Adhanom Ghebreyesus has recently said that 'Theend of the pandemic is near. We are not there yet, but the end is in sight'. And U.S.President Joe Biden, with about 400 deaths per day in the U.S., has repeated thatassertion. From what we can read in the literature, we are not there yet and theremay be a long way to go. Although more is known about the virus and its ability totransform into variants and subvariants in order to enter the host more easily, someof these transformations are cause for concern. We make a brief review of what wehave learned about morbidity and mortality due to SARS-CoV-2, how women's healthhas worsened, some alterations in sperm, defenses against the virus, reinfections, itsunhealthy action on the pregnant woman, the fetus and the newborn, vaccines andboosters, and a vision of what lies ahead.